’n Ondersoek na die taalgebruik in Son as verteenwoordigend van Kaaps - Blignaut, Joline; Lesch, Harold (Stellenbosch Papers in Linguistics Plus, 2015)
<!–[if gte mso 9]> Normal 0 MicrosoftInternetExplorer4 <![endif]–> Opsomming Kaaps is een van die oudste variëteite van Afrikaans wat sedert die sewentiende eeu aan die Kaap gepraat is en is vandag steeds die taal van die bruin werkersklas in die Kaapse Skiereiland. Alhoewel dit hoofsaaklik as ŉ gesproke variëteit gebruik word, word dit ook aangewend in die letterkunde. Dis veral die gebruik van Kaaps in die digkuns en drama van Adam Small wat Kaaps help vestig het in die Afrikaanse literatuur en ŉ nuutgevonde belangsteling in dié variëteit van Afrikaans gebring het. Vandag vind Kaaps neerslag in die teater, musiek, televisie, radio en die gedrukte media. Die doel van die studie is om die gebruik van Kaaps in die poniekoerant Son te ondersoek. Die studie wil bepaal tot watter mate Kaaps in die Son-artikels gebruik word en tot watter mate diglossie voorkom in Son deur die gebruik van Kaaps en Standaardafrikaans in een artikel of binne een uitgawe van Son. Die taalvariasie in Son word vanuit ŉ sosiolinguistiese raamwerk ondersoek as verteenwoordigend van Kaapse Afrikaans. Binne die raamwerk word taal binne die sosiale konteks waarbinne dit voorkom ondersoek. ŉ Gelykevlakbenadering tot taalvariasie word gevolg waar Kaaps beskou word as deel van die spektrum van Afrikaans en nie as ondergeskik tot die standaardvariëteit nie. Son is die eerste Afrikaanse poniekoerant in Suid-Afrika en die eerste koerant wat ŉ informele vorm van Afrikaans gebruik wat deur sommige beskou word as Kaaps. Die doel van die studie is om die taalgebruik in Son te ondersoek in ŉ poging om te bepaal tot watter mate die taalgebruik in Son ŉ getroue weerspieëling van Kaaps is en tot watter mate dit ooreenstem met die taalgebruik van die sprekers van Kaaps. Die ondersoek word gedoen deur ŉ teksanalise van Son-artikels uit verskillende uitgawes van Son. Die bevinding van die studie is dat die taalgebruik in Son nie beskou kan word as ŉ ware weerspieëling van Kaaps nie, maar eerder as ŉ informele Afrikaans wat elemente van Kaaps bevat. Research to establish whether the language usage in Son is indicative of Kaaps Extended abstract Kaaps is one of the oldest dialects of Afrikaans that originated in the Cape Colony during the seventeenth century and is still used today by the working class Coloured community of the Cape Peninsula. Although Kaaps is used mainly as a spoken dialect, it is also applied in the literature. In the 1940s, Kaaps was applied in the prose of S.V. Petersen and later, in the 1960s in the work of Adam Small who established Kaaps in the Afrikaans literature and brought a newfound interest in the dialect. Today the use of Kaaps in its written form is no longer restricted to the literature, but is also reflected in theatre, music, television and the printed media. The focus of this study is to investigate the use of Kaaps in the Afrikaans tabloid, Son. Studies of the written representation of Kaaps are mainly restricted to research that examined the use of this dialect in literature or drama. This includes studies by Hendricks (1978) and Coetzee (2005). A linguistic examination of the use of Kaaps in tabloids has not been conducted yet. The aims of this study were to determine to what extent Kaaps is used in Son articles and to what extent the written language correlates with the spoken Kaaps, as its speakers use it, as well as whether it is representative of Kaaps. The study also aimed to determine to what extent a diglossic relationship exists in Son by the use of both Kaaps and Standard Afrikaans in one article or in one entire issue of Son. This study followed a sociolinguistic approach to describe the relationship between language and society and examined language in the social context in which it is used. With this approach, Kaaps is no longer seen as inferior to the standard variety of Afrikaans, but rather as part of the greater spectrum of Afrikaans. Son is the first and only Afrikaans tabloid in South Africa. It was published for the first time in 2003 as a weekly publication after which it became available as a daily newspaper in 2005. Currently Son appears in the Western- and Eastern Cape and its target market is lower income Coloured Afrikaans communities. According to Botha (2009), three characteristics distinguish tabloids from other newspapers, namely news themes, language and style. Tabloid articles cover stories about scandal, gossip, sex and crime, and use informal language and writing styles, as well as crude language. Son contains community stories about issues that readers can identify with, for instance poverty, unemployment and gang- and drug related crime. An informal Afrikaans is used in Son that many regard as Kaaps. According to Edwin Lombard, assistant editor of Son, the journalists of Son aim to use a language in their articles that resembles the language that is used by its readers. Anastasia de Vries (2012) regards the language that is used in Son as an unedited language document of Kaaps “as she is spoken”. Although many people view the language that is used in Son as Kaaps, no evidence could be found of linguistic investigation carried out to determine the extent to which the language that is used in Son correlates with the Kaaps used by its speakers. A linguistic investigation into the language that is used in Son was done by means of a text analysis of various Son articles that appeared in different issues of Son. The investigation aimed to determine the extent to which Kaaps is used in Son and if the language that is used in Son can be regarded as representative of Kaaps. Kaaps is characterised by a substantial English influence. This includes mixing of English and Afrikaans lexemes, borrowing lexemes from English and the Afrikaansifying of English words e.g. [ᴐldœu] (although) or [xǝtra:i] (try). The lexicon also comprises influences from the Muslim community with words like salaam that is a greeting form in Kaaps. The use of existing words in new or extended meanings is also typical lexical markers of Kaaps. This includes words like gevaarlik (dangerous) or duidelik (clear) with the meaning of good or nice, e.g. Hy speel [xǝfa:lǝk] (good) rugby. Furthermore Kaaps contains certain expressions that are characteristic of this dialect, for example Kom ons [ma:ts] (march) meaning let’s go. Phonological features of Kaaps include vowel raising, e.g. [uk] (ook); schwa lowering, e.g. [xakᴐm] (gekom); affrication, e.g. [dӡǝi] (jy) and post-vocalic /r/-deletion, e.g. [vɛk] (werk). Syntactical features of Kaaps include the use of the definite article die (the) before names of localities and the doubling of in (in) as a preposition and postposition, e.g. Ek bly in die Lavender Hill in. Morphologically, Kaaps also varies from Standard Afrikaans. This involves the embedding of the Afrikaans past tense form (ge-) in the English word, e.g. ge-worry, as well as the redundant addition of post morpheme to adjectives, e.g. bietere, pronounced as [bitǝrǝ] for beter (better), oralster pronounced as [oralstǝ] for oral (everywhere), and to verbs like skrywe for skryf (write). The findings of this study is contrary to the view of, among others, Lombard and De Vries (2012) that the language that is used in Son is not a true representation of Kaaps, but rather an informal Afrikaans that use elements of Kaaps. The most important characteristic of the language that is used in Son is the mixing of English and Afrikaans words. English words appear frequently in the articles, e.g. “Die counsil kan mos ons subsidy wegvat en eerder vir ons grond gee” (Son, 31 October 2012, p.6) (The council can take away our subsidy and rather give us land). Although the mixing of English and Afrikaans is one of the most prominent features of Kaaps, the great extent of English influence is also the most prominent feature of demotic Afrikaans. Therefore the language that is used in Son cannot be regarded as exclusively Kaaps. Linguistic features of Kaaps are also present in the articles of Son, but are not used as frequently as English words and elements. Linguistic features of Kaaps are restricted to lexical items and expressions. The following are examples of typical lexical markers and expressions that are used in Son articles: “Dansonnie mang lewenslank na rape” (Son, 1 November 2012, p.2) (Dance instructor sent to jail for life after rape) and “Van 2 tot 4 Maart gaan die ding ruk” (Son, 16 February 2012, p.2) (From the 2nd to the 4th of March things will get jolly). Although lexical markers of Kaaps are present in Son articles, English words are often used instead of their Kaaps lexical equivalent. Lexical markers of Kaaps that are used in the tabloid are also mainly restricted to the direct words of sources and readers and, to a lesser extent, to those of reporters. The analysis of the language that is used in Son revealed that there is a link between the content of the article and the language that is used. Lexical markers and expressions of Kaaps are used in articles that deal with community stories, gossip- and sensational reports. Contrary to this, Standard Afrikaans is used in prime news and especially in sport reports. At a grammatical level, the language that is used in the articles of Son does not reflect the syntactical features of Kaaps. Except for the influence of English on the word formation of Afrikaans words, the morphological features of Kaaps are not reflected in the articles of Son. Phonological variations of Kaaps are rarely reflected in the spelling of words. In the few instances where phonological variations are used, they are applied for humour’s sake or to draw attention. Some articles of Son, such as the prime news and sport reports, are written exclusively in Standard Afrikaans. A diglossic relationship exists in Son articles, as well as in the entire issue of Son, in that some articles are written in the high variety (Standard Afrikaans), while other articles use a low variety or demotic Afrikaans that is an informal Afrikaans, with lexical markers of Kaaps. A diglossic relationship also exists in one article, as demotic Afrikaans is alternated by Standard Afrikaans expressions and words. This alternation between Standard Afrikaans, Kaaps and demotic Afrikaans is typical of the way the speakers of Kaaps alternate between these varieties of Afrikaans, which shows the linguistic repertoire of the speakers of Kaaps. By using different varieties of Afrikaans, the tabloid represents a bigger speaker corps and includes more readers. Given the diglossic relationship that exists in Son and the absence of phonological, syntactical and morphological markers of Kaaps, as well as the absence of lexical markers of Kaaps in some articles and the low frequency which Kaaps words and expressions are used in other articles, the language that is used in Son cannot be seen as a true reflection of Kaaps, but rather as an informal demotic Afrikaans that use elements of Kaaps. <!–[if gte mso 10]> <![endif]–>